2019
DOI: 10.3389/fimmu.2019.00730
|View full text |Cite
|
Sign up to set email alerts
|

Adeno-Associated Virus as an Effective Malaria Booster Vaccine Following Adenovirus Priming

Abstract: An ideal malaria vaccine platform should potently induce protective immune responses and block parasite transmission from mosquito to human, and it should maintain these effects for an extended period. Here, we have focused on vaccine development based on adeno-associated virus serotype 1 (AAV1), a viral vector widely studied in the field of clinical gene therapy that is able to induce long-term transgene expression without causing toxicity in vivo . Our results show the potential utilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
35
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(41 citation statements)
references
References 56 publications
(73 reference statements)
4
35
1
Order By: Relevance
“…The transgenic P. berghei Pfs25DR3 ( Pb Pfs25DR3) that was used for TB assays and the ookinete immunofluorescence assays (IFAs) was kindly donated by A. Blagborough from Imperial College London (22). The transgenic P. berghei expressing PfCSP (PfCSP-Tc/Pb) that was used for the IFAs and the protective efficacy study was described previously (2123). Both transgenic parasites were maintained in the Laboratory of Vaccinology and Applied Immunology, Kanazawa University.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The transgenic P. berghei Pfs25DR3 ( Pb Pfs25DR3) that was used for TB assays and the ookinete immunofluorescence assays (IFAs) was kindly donated by A. Blagborough from Imperial College London (22). The transgenic P. berghei expressing PfCSP (PfCSP-Tc/Pb) that was used for the IFAs and the protective efficacy study was described previously (2123). Both transgenic parasites were maintained in the Laboratory of Vaccinology and Applied Immunology, Kanazawa University.…”
Section: Methodsmentioning
confidence: 99%
“…For the generation of AdHu5-Pfs25-PfCSP, the gene encoding Pfs25 and the Gly6Ser hinge was excised from pUC57-Simple-sPfs25-hinge (21) by digestion with EcoRI/MefI and then inserted into the EcoRI site of pENTR-D-sPfCSP2-G2-sWPRE (23) to construct pENTR-D-fusion. Pfs25-PfCSP was excised by digestion of pENTR-D-sPfs25-sPfCSP-WPRE with EcoRI/XmaI and then inserted into the EcoRI/XmaI sites of pENTR-CAG-sPfCSP2-G2-sWPRE (21) to construct pENTR-CAG-sPfs25-sPfCSP2-G2-sWPRE, which was subsequently cloned into the shuttle vector pAd/PL-DEST (Invitrogen, Carlsbad, CA, USA) using a Gateway cloning technology. The adenovirus was purified and titrated as described previously (24).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most TBVs rely on host antibodies ingested during blood feeding, along with Plasmodium parasites, that bind to proteins on the surface of the parasite and block transmission by inhibiting parasite development ( Sauerwein and Bousema, 2015 ; Schorderet-Weber et al, 2017 ). Over the last 20 years, a number of antigens, including Pfs230 ( MacDonald et al, 2016 ; Marin-Mogollon et al, 2018 ; Scaria et al, 2019 ), Pfs48/45 ( Theisen et al, 2014 ; Singh et al, 2017 , 2019 ; Cao et al, 2018 ; Lennartz et al, 2018 ), and Pfs25 in Plasmodium falciparum as well as its ortholog Pvs25 in Plasmodium vivax ( Miura et al, 2007 ; Lee et al, 2016 ; Blagborough et al, 2016 ; Brune et al, 2016 ; Leneghan et al, 2017 ; Parzych et al, 2018 ; Thompson et al, 2018 ; McLeod et al, 2019 ; Yusuf et al, 2019 ), have been identified as potential vaccine targets. Preclinical and clinical studies have shown that TBVs hold the promise to reduce malaria transmission and raise the prospect of providing an additional effective tool toward malaria eradication ( Chichester et al, 2018 ; Sagara et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%